CD27 as a Diagnostic Biomarker and Its Role in Immune Heterogeneity and Predicting Clinical Drug Responses in Hashimoto’s Thyroiditis - Dong YM; Bao GQ (Pharmacogenomics and Personalized Medicine)
Yan-ming Dong, Guo-qiang Bao Department of General Surgery, The Second Affiliated Hospital of Air Force Medical University, Xi’an, Shaanxi Province, People’s Republic of ChinaCorrespondence: Guo-qiang Bao, Department of General Surgery, The Second Affiliated Hospital of Air Force Medical University, No. 356 of Xinsi Road, Baqiao District, Xi’an, Shaanxi Province, People’s Republic of China, Tel +86 13891430409, Email baoguoqiang_ln@163.comObjective: To identify key genes and potential molecular mechanisms associated with Hashimoto’s thyroiditis (HT) to provide new insights for the development of diagnostic and therapeutic targets for this disease.Methods: Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were conducted to identify the differentially expressed genes (DEGs) associated with HT. A protein-protein interaction (PPI) network was used to obtain hub genes, with CD27 emerging as the key gene in HT. Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, Gene Set Enrichment Analysis (GSEA), and HT-infiltrating immune cell components as well as functions were performed to further investigate the role and potential mechanism of CD27 in cohorts with high and low expression of CD27.Results: CD27 was found to be upregulated in HT tissues and showed considerable clinical utility in HT. The CD27 of the high-expression cohort exhibited a higher enrichment in immune-related biological processes than the low-expression group. Cell-type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT) analysis revealed that several activated HT-infiltrating immune cells were strongly associated with CD27, suggesting that CD27 has the potential to be a marker for the immune state in HT.Conclusion: In our study, CD27 was found to contribute to predicting clinical outcomes in patients with HT, including disease status and response to immunotherapy. CD27 is a promising biomarker for HT microenvironment remodeling, offering insights into new therapeutic approaches to improve treatment of HT.Keywords: CD27, diagnosis, drug response, Hashimoto’s thyroiditis, immune heterogeneity